The Prevalence of Pseudomonas aeruginosa among Baghdad Hospitalised Patients (Medico Legal Update, 2021)
In order to determine the prevalence of Pseudomonas aeruginosa among hospitalised patients, 156specimens were collected from hospitalized patients referring Baghdad, Iraq hospitals. Bacterial isolateswere identified using conventional biochemical tests and then identification was confirmed by the locating of16SrRNA. Pseudomonas aeruginosa constitutes 30.05%. In conclusion, the attention should be paid towardthe infections of this opportunistic pathogen.